Description of Releted Magical Beliefs and Practices with Medicine - García Arroyo, José Manuel (MEDICA REVIEW. International Medical Humanities Review / Revista Internacional de Humanidades Médicas, 2019)
In our midst the magic behaviors are more frequent than we think, particularly in the territory of medicine and this work is dedicated to their study. To achieve this, we talked with the patients who have come to consult the Association of Psychopathology and Psychoanalysis of Seville (APPS) and, in the intimate atmosphere of the consultation, could express with tranquility an issue that can not be spoken outside a private context. The result has been the description of six groups of magical beliefs, which violate the principles of logical thinking (spell, possession, loss of soul, etc.). At the same time, these initiate remedies that are carried out by healers and healers (exorcisms, amulets, spells, etc.). The doctor must know the existence of these behaviors to be able to act correctly in front of them and not to err in their diagnoses.